Increased Expression of Thymosin β Is Independently Correlated with Hypoxia Inducible Factor-1α (HIF-1α) and Worse Clinical Outcome in Human Colorectal Cancer - Seung Yun Lee; Mee Ja Park; Hye Kyung Lee; Hyun Jin Son; Chang Nam Kim; Joo Heon Kim; Dong Wook Kang (Journal of Pathology and Translational Medicine, 2017)
Background Thymosin β4 is a multi-functional hormone-like polypeptide, being involved in cell migration, angiogenesis, and tumor metastasis. This study was undertaken to clarify the clinicopathologic implications of thymosin β4 expression in human colorectal cancers (CRCs). Methods We investigated tissue sections from 143 patients with CRC by immunohistochemistry. In addition, we evaluated the expression patterns and the clinico-pathological significance of thymosin β4 expression in association with hypoxia inducible factor-1α (HIF-1α) expression in the CRC series. Results High expression of thymosin β4 was significantly correlated with lymphovascular invasion, invasion depth, regional lymph node metastasis, distant metastasis, and TNM stage. Patients with high expression of thymosin β4 showed poor recurrence-free survival (p = .001) and poor overall survival (p = .005) on multivariate analysis. We also found that thymosin β4 and HIF-1α were overexpressed and that thymosin β4 expression increased in parallel with HIF-1α expression in CRC. Conclusions A high expression level of thymosin β4 indicates poor clinical outcomes and may be a useful prognostic factor in CRC. Thymosin β4 is functionally related with HIF-1α and may be a potentially valuable biomarker and possible therapeutic target for CRC.